1994
DOI: 10.1152/jappl.1994.77.3.1431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing work rate on metabolic responses of the donkey (Equus asinus)

Abstract: Oxygen consumption (VO2) and concentration of venous blood metabolites were measured in donkeys trained to run and to pull loads on a treadmill. VO2 in two donkeys running at maximal speed on a 9.8% slope was 110 +/- 2 ml.min-1.kg-1, approximately 22 times preexercise VO2. Average heart rate at maximal VO2 (VO2max) was 223 +/- 2 beats/min, five times the preexercise heart rate. Blood lactate increased 14-fold, and blood glucose did not change (P > 0.05). Animals running up a 4% incline and incremental draft lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 0 publications
2
17
1
Order By: Relevance
“…At the highest tread speed in this study the average metabolic scope was 6:1 for camels and 5:1 for donkeys. The metabolic scopes recorded in this study indicated a moderate level of energy expenditure when compared to maximum metabolic scopes of 32:1 and 22:1 in camels and donkeys, respectively Mueller et al, 1994). These findings in combination with the low COT tot and COT net recorded in this study verify economic energy expenditure in camels and donkeys at moderate speeds of locomotion.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…At the highest tread speed in this study the average metabolic scope was 6:1 for camels and 5:1 for donkeys. The metabolic scopes recorded in this study indicated a moderate level of energy expenditure when compared to maximum metabolic scopes of 32:1 and 22:1 in camels and donkeys, respectively Mueller et al, 1994). These findings in combination with the low COT tot and COT net recorded in this study verify economic energy expenditure in camels and donkeys at moderate speeds of locomotion.…”
Section: Discussionsupporting
confidence: 70%
“…Each animal's locomotory performance reflects important aspects of its physiological, morphological and behavioural characteristics (Schmidt-Nielsen, 1972;Taylor et al, 1982;Dickinson et al, 2000;Rubenson et al, 2007). Camels are capable of long treks at fast speeds (32 km at 6 m s À1 ) with no signs of fatigue and donkeys are noted for their ability to perform strenuous work (Yousef et al, 1972;Mueller et al, 1994). Metabolic scope, the ratio of peak metabolic rate ( _ VO 2 max ) to resting _ VO 2 , is about 10:1 for most mammals (Schmidt-Nielsen, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Although we acknowledge the dangers of extrapolation, using the second-order polynomial equation relating EE tot to walking speed (R 2 0.88; Fig.2), we estimate that it would require a 26-fold increase EE tot above rest (Table1) for the Asian elephants reported here to walk at 6.8ms -1 . The estimated increase in EE tot in fast-walking elephants is comparable to near-maximum increases in energy expenditure recorded in donkeys and camels of 22-and 32-fold, respectively (Evans et al, 1994;Mueller et al, 1994).…”
Section: Optimum Walking Speed In Asian Elephantssupporting
confidence: 57%
“…Blood samples were taken as part of full clinical assessment to ensure that the donkeys were fit for rehoming. To exclude stress effects on the measured parameters, heart rate, respiratory rate, pulse and rectal temperature were measured before the blood collection (Mueller et al, 1994). Two blood samples were drawn from the jugular vein of the examined donkeys into 2 ml EDTA vacutainer tubes for haematological analysis and 10 ml plain vacutainers tubes for serum biochemical analysis.…”
Section: Animals and Sample Collectionmentioning
confidence: 99%